Propuesta de conjunto de herramientas de documentación de administración de proyectos de construcción en Hacienda Pinilla. - Retana-Rivera, Kenneth (Instituto Tecnológico de Costa Rica, 2011)
This project proposes a tool kit for the documentation of the construction project management in Hacienda Pinilla. It aims to solve the problem of lack of control of information in the organization under study. One of the characteristics sought in the tool kit proposed was simplicity in the deployment and use in projects of the company, since otherwise the organization would not make the effort to incorporate the proposed tools. This tool kit uses as the basis the proposal by the Project Management Body Of Knowledge (PMBOK ®) from the Project Management Institute (PMI), taking into account the simplicity. The processes and documents submitted by the PMBOK ® were analyzed, considering their applicability to construction projects and the company under study. It is proposed that from this analysis the format of the documents should function as a standard guide for the company to document their construction projects. The overall objective of this project is achieved by solving the problem identified in the company with a basic documentation tool kit in accordance with globally accepted practices proposed by the PMI and staying on a simple level and needing a minimum effort to implement it.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica de Gerencia de Proyectos, 2011.
Keywords: Tiempo; Costos; Riesgos; Integración; Recursos humanos; Comunicaciones